UKURAN PERUSAHAAN MEMODERASI FAKTOR-FAKTOR YANG MEMPENGARUHI TAX AVOIDANCE - Sri Ayem; Violieta Annisa Titania (Edunomic : Jurnal Ilmiah Pendidikan Ekonomi Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This study aims to examine the effect of capital intensity, real earnings management and political connections on tax avoidance with company size as a moderating variable. This study uses a population of property and real estate sector companies listed on the Indonesia Stock Exchange. The data in this study are secondary data obtained from the company's annual financial statements in 2020 - 2022. The sampling method uses purposive sampling technique, the population that will be used as a research sample is a population that meets certain criteria. The sample of companies that met the research criteria was 28 companies. The outlier data is 10 financial statement data. This study uses multiple linear regression analysis models and Moderated Regression Analysis (MRA) analysis with the SPSS version 25 program. The results showed that capital intensity and political connections have a negative effect on tax avoidance. While real earnings management has a positive effect on tax avoidance. Company size cannot weaken the influence of capital intensity, real earnings management and political connections on tax avoidance.